ANALISIS SPASIAL DETERMINAN PERTUMBUHAN INKLUSIF KABUPATEN/KOTA DI PROVINSI JAWA TENGAH TAHUN 2017 - Tju Ji Long; Ernawati Pasaribu (Seminar Nasional Official Statistics, 2019)
The high economic growth of Central Java but still followed by high rates of poverty and uneven distribution of income indicate that the economic growth of Central Java has not been of high quality. To obtain quality economic growth, a concept of inclusive growth is needed. This study aims to measure and analyze the determinants of inclusive growth in the districts/cities in Central Java in 2017 with a spatial analysis approach. The results of the study show that there are three regions that have low inclusive growth, 15 regions with moderate inclusive growth, and 17 regions with high inclusive growth. In addition, the results of spatial regression shows that the PMTB and government expenditure on social protection functions have a positive and significant effect on inclusive growth. UMK has a negative and significant effect on inclusive growth. Meanwhile, inflation and government spending on the education function have a negative and insignificant effect on inclusive growth. Futhermore, there are spatial linkages in inclusive growth of the districts/cities in Central Java. Thus, inclusive growth in certain districts/cities will affect the inclusive growth of the districts/cities around them.